Microsociology and macropolitics in criminological positivism: bases for reflection in the light of critical criminology (Revista do Tribunal Regional Federal da 3ª Região, 2022)
And why have the effects of criminological positivism persisted for so many years? What does scientism have to do with this positivism? Why does this theory survive to this day despite its inconsistencies? In order to reflect on these questions, it is necessary to establish the parameters of the consensus society, at the root of which lies positivism and also authoritarianism. This worldview is based on the idea that people are united in society by a consensus, in other words, by a single shared reality, so that anything that interferes with this reality is the product of defects in the processes that lead to the formation of consensual harmony. In this way, crime is not seen as inherent to society, but, quite the opposite, as the result of insufficient socialization mechanisms that lead to conformity.
Keywords: Microsociology; Macropolitics; Criminological positivism; Critical criminology